Stability Analysis of Nonlinear Systems with Impulsive Perturbations: Application to Hopfield Neural Networks - Benjemaa, Mondher; Gouadri, Wided; Hammami, Mohamed Ali (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we provide some sufficient conditions for the asymptotic stability of solutions of nonlinear dynamic systems with impulsive perturbations by using some inequality of Gronwall type. Practical exponential stability is also investigated for a class of perturbed impulsive systems. Several numerical examples are provided to demonstrate the effectiveness of the theoretical results. Furthermore, Hopfield neural networks system is discussed as an application.